Nurse-patient interaction and self-transcendence: assets for a meaningful life in nursing home residents? - Haugan, Gørill (BMC Geriatr, 2020)
BACKGROUND: Due to the shift to an older population worldwide and an increased need for 24-h care, finding new and alternative approaches to increase wellbeing among nursing home (NH) residents is highly warranted. To guide clinical practice in boosting wellbeing among NH residents, knowledge about nurse-patient interaction (NPI), inter- (ST1) and intra-personal (ST2) self-transcendence and meaning-in-life (PIL) seems vital. This study tests six hypotheses of the relationships between NPI, ST1, ST2 and PIL among cognitively intact NH residents. METHODS: In a cross-sectional design, 188 (92% response rate) out of 204 long-term NH residents representing 27 NHs responded to NPI, ST, and the PIL scales. Inclusion criteria were: (1) municipality authority’s decision of long-term NH care; (2) residential time 3 months or longer; (3) informed consent competency recognized by responsible doctor and nurse; and (4) capable of being interviewed. The hypothesized relations between the latent constructs were tested through structural equation modeling (SEM) using Stata 15.1. RESULTS: The SEM-model yielded a good fit (χ2 = 146.824, p = 0.021, df = 114, χ2/df = 1.29 RMSEA = 0.040, p-close 0.811, CFI = 0.97, TLI = 0.96, and SRMR = 0.063), supporting five of the six hypothesized relationships between the constructs of NPI, ST1, ST2 and PIL. CONCLUSION: NPI significantly relates to both ST1, ST2 and PIL in NH residents. ST revealed a fundamental influence on perceived PIL, while NPI demonstrated a significant indirect influence on PIL, mediated by ST.